2014
DOI: 10.1128/aac.02918-14
|View full text |Cite
|
Sign up to set email alerts
|

Phenyl-1-Pyridin-2yl-Ethanone-Based Iron Chelators Increase IκB-α Expression, Modulate CDK2 and CDK9 Activities, and Inhibit HIV-1 Transcription

Abstract: dHIV-1 transcription is activated by the Tat protein, which recruits CDK9/cyclin T1 to the HIV-1 promoter. CDK9 is phosphorylated by CDK2, which facilitates formation of the high-molecular-weight positive transcription elongation factor b (P-TEFb) complex. We previously showed that chelation of intracellular iron inhibits CDK2 and CDK9 activities and suppresses HIV-1 transcription, but the mechanism of the inhibition was not understood. In the present study, we tested a set of novel iron chelators for the abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 58 publications
(79 reference statements)
2
12
0
Order By: Relevance
“…Treatment with ferric ammonium citrate further increased HIV-1 inhibition in SCD PBMCs but had no effect on HIV-1 infection in control PBMCs (Figure 2E, iron). Treatment with iron chelator, PPYeT, 25 inhibited HIV-1 replication in control PBMCs in accord with our previous study, 25 and further inhibited HIV-1 in SCD PBMCs (Figure 2E, chelator). These observations suggested that iron metabolism was altered in SCD PBMCs, and that iron depletion by an iron chelator or ferroportin inhibited HIV-1.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Treatment with ferric ammonium citrate further increased HIV-1 inhibition in SCD PBMCs but had no effect on HIV-1 infection in control PBMCs (Figure 2E, iron). Treatment with iron chelator, PPYeT, 25 inhibited HIV-1 replication in control PBMCs in accord with our previous study, 25 and further inhibited HIV-1 in SCD PBMCs (Figure 2E, chelator). These observations suggested that iron metabolism was altered in SCD PBMCs, and that iron depletion by an iron chelator or ferroportin inhibited HIV-1.…”
Section: Resultssupporting
confidence: 91%
“…Intracellular iron levels were then analyzed using calcein fluorescent sensor. 25 PBMCs were treated with nonfluorescent cell-permeable calcein AM, which is converted to calcein in the cells whose fluorescence is quenched upon binding to iron. A fractional fluorescence (F − F 0 )/F, which is inversely proportional to the amount of labile chelatable iron, was markedly higher in SCD PBMCs (Figure 3B), suggesting a reduced LIP in SCD PBMCs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations